Prognostic implication of right ventricular-pulmonary artery coupling in valvular heart disease - Wu, Zhenni; Xie, Mingxing; Zhang, Li; He, Qing; Gao, Lang; Ji, Mengmeng; Lin, Yixia; Li, Yuman (Frontiers in Cardiovascular Medicine, 2025)
Valvular heart disease (VHD) leading to inadequate hemodynamic circulation is a major cause of cardiovascular morbidity and mortality worldwide. Right ventricular-pulmonary artery (RV–PA) coupling integrates the ability of RV contractility to adapt to increased pulmonary arterial afterload. If the right ventricle cannot adapt to the elevated afterload by increasing its contractile function, RV-PA uncoupling occurs. RV-PA uncoupling has been shown to be associated with poor outcomes in VHD. This review summarizes the prognostic significance of RV-PA coupling in patients with VHD.